Pengaruh Kompres Hangat Terhadap Rasa Nyeri Persalinan Kala I Fase Persalinan Fase Aktif di 3 BPM Kota Cirebon - Fitrianingsih, Yeni; Wandani, Kemala (Care : Jurnal Ilmiah Ilmu Kesehatan, 2018)
Pain is the most dominan the first stage of childbirth. Pain of labor it can cause stress that causes, so it causing the release of hormone much like katekolamin and steroids. Excessive hormone secretion will cause Impaired uteroplacental circulation Thus causing hypoxia in the fetus. One for controlling labor pain by non-pharmacological methods that is warm compress Objective: to know The influence of warm compressesto pain in the first stage of the active phase Independent midwives cirebon city Methods: This research method Using design quasy eksprerimen design pre and post one group design The study sample is first stage of childbirth in independent midwifes city cirebon As many thirty respondents The data used in this study is the primary data Primary using a questionnaire given directly to the respondent. Stages of data analysis used are univariate and bivariate. Results: The result of the analysis shows the value of coefficient Z of 4,820 and Asym.Sig (p value) of 0.000. This shows that the value of Asym.Sig (p value)